“I am an Old Car, My Engine is not Powerful Anymore,” A Senior Teacher’s Voice on his ICT Learning, Obstacles and Its’ Implications for Teachers’ Development - Adi Suryani (International Journal of Pedagogy and Teacher Education, 2017)
The infiltration of ICT into education sector is inevitable. ICT can assist teachers in their teaching and learning practices. However, some teachers may not digital natives who are ready and can learn ICT quickly or happy to learn it naturally and effortlessly. Difficult choice between staying in comfort zone or following technological changes frequently happens to old (senior) teachers. For them, this era can be different from their era. Consequently, they may feel the tension of transition between convention or how they usually do and modernity or follow recent technological changes. This paper aims to explore a senior teacher’s feeling and thinking on his ICT learning efforts, forces, pressures, obstacles and its’ consequences for teachers’ learning and development or what we (other teachers) can reflect on his ICT learning experiences. The data are collected through interview and written response. The data show that the teacher is struggling to learn up-dated ICT and adapt to changes. He is trying to go across the border of his comfort zone. However, during his ICT learning process, he is restrained by his own self-constraints, including internal motivation, lack of self-confidence, age, energy and capacity to learn. He also finds obstacles and pressures from his social and physical surroundings. Social comparison, emerging conflict, unsupportive team culture and lack of external motivation are several restrictions of his ICT learning. This indicates that ICT learning needs more than knowledge/cognition on the technical operation, but it involves a broader spectrum of learning: affective, social, situated, self-directed and experiential learning.